KAJIAN PENGGUNAAN DANA DESA DALAM PROGRAM PEMBERDAYAAN MASYARAKAT DI KECAMATAN SONDER - Ferly Rayen Runtu; Caroline Betsi Diana Pakasi; Lyndon Reindhardt Jacob Pangemanan (Sam Ratulangi University, 2019)
Â The purpose of this study was to determine the use of village funds in community empowerment programs in 8 villages, which were chosen deliberately (purposive sampling) from 19 villages in Sonder District. This research lasted for 2 months from October to November 2018. The data used in this study are primary data and secondary data. Primary data is data obtained from interviews with 4 respondents per village selected based on accidental sampling so that the total number of respondents from 8 villages is 32 community members. The interview was intended to find out the opinion of the community about the use of village funds. Secondary data in this study is data obtained from the APBDES document (Village Budget and Revenue). Data analysis method in this research uses descriptive method. The results showed the use of village funds in Sonder Subdistrict for physical programs amounted to 14 types of activities and for empowerment programs amounted to 15 types of activities. Therefore the total activities amounted to 29 activities. The opinion of the community who stated agreed on the openness of the village government to the village funds amounted to 68.75% and 31.25% of the community stated disagree. The community stated that they agreed to use the village funds for development programs amounted to 75%Â and 25% of the community disagreed. The opinion of the community that stated that the development program was approriate amounted to 78.12% and 22.88% of the community stated that it was not appropriate. *eprm*Â